USE OF COMMUNITY HEALTH WORKERS AND PATIENT NAVIGATORS TO IMPROVE AND PLANNING AND OF HEALTHCARE SYSTEM - Noura Mudhi Alwan Al-Qarni; Samar Jaber Ahmed Al-Absi; Nadia Jaber Ahmed Abu Habira; Rabab Ali Majrashi; Reema Salem Alenzi; Samar Shoei Barakat; Ahmed Adwan Zaid Al-Shammari; Hadiah ashowi alanazi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: The evolving landscape of healthcare emphasizes the importance of involving health workers and patients in the planning and development of healthcare services. This approach has been linked to improved healthcare outcomes, increased satisfaction, and more efficient service delivery. The aim of this systematic review was to examine the impact of such involvement on the quality and efficacy of healthcare services.Methods: A comprehensive search strategy was employed across multiple databases including PubMed, Scopus, Web of Science, and the Cochrane Library, focusing on interventional studies and clinical trials published in English from 2007 to 2 022. Inclusion criteria were set to select studies that involved health workers and/or patients in healthcare planning and development, with clear outcomes related to effectiveness, efficiency, patient satisfaction, or worker satisfaction. Studies were excluded if they were non-interventional, lacked relevant outcomes, or fell outside the publication timeframe. The selection process involved screening titles and abstracts, followed by a full-text review, with disagreements resolved through discussion or third- party adjudication.Results: Eleven studies met the inclusion criteria, demonstrating a range of interventions from participatory workshops to digital feedback platforms. Key findings include a 25% increase in patient satisfaction (risk ratio [RR] 1.25), a 15% reduction in unnecessary diagnostic procedures (RR 0.85), a 20% improvement in adherence to clinical guidelines (RR 1.20), and a 25% decrease in hospital readmission rates for chronic disease patients (RR 0.75).Conclusions: The review provides compelling evidence that involving health workers and patients in the planning and development of healthcare services leads to significant improvements in patient satisfaction, healthcare efficiency, and clinical outcomes. These findings underscore the value of participatory healthcare practices, suggesting that healthcare providers should integrate these approaches to enhance the quality and effectiveness of care delivery.